1985
DOI: 10.1113/jphysiol.1985.sp015812
|View full text |Cite
|
Sign up to set email alerts
|

Calcium regulation of potassium fluxes in rabbit aorta during activation by noradrenaline or high potassium medium.

Abstract: SUMMARY1. The dependency of noradrenaline-and depolarization-mediated increases in K permeability on cellular Ca was investigated by measuring the effect of diltiazem and Ca-free medium on stimulated 42K efflux and contracture.2. The increase in the rate constant (k) for 42K efflux induced by cellular depolarization with 80 mM-K was inhibited by 70 % in the presence of 10-5 M-diltiazem. The noradrenaline (NA)-mediated increase in k was only slightly suppressed by diltiazem at 10-5 M-NA, but was inhibited by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

1987
1987
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
2
14
1
Order By: Relevance
“…Inasmuch as the response of arterial smooth muscle to high concentrations of K+ is known to depend on transmembrane Ca2+ influx (Bolton, 1979), the inhibition by pinacidil of contractions induced by high concentrations of K+ may reflect an action of this drug in inhibiting Ca2+ influx. Furthermore, this action of pinacidil will have a great influence on the Ca2 +-activated K+ channels as has been demonstrated for other Ca2 + influx inhibitors (Casteels & Droogmans, 1985;Aaronson & Jones, 1985). In contrast with these observations, it was demonstrated that high concentrations (30 and 100 yM) of pinacidil had little or no effect on 80mM K+-induced contractions in rat aorta (Bray et al, 1987; C) Macmillan Press Ltd, 1990 Weston et al, 1988).…”
Section: Introductioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Inasmuch as the response of arterial smooth muscle to high concentrations of K+ is known to depend on transmembrane Ca2+ influx (Bolton, 1979), the inhibition by pinacidil of contractions induced by high concentrations of K+ may reflect an action of this drug in inhibiting Ca2+ influx. Furthermore, this action of pinacidil will have a great influence on the Ca2 +-activated K+ channels as has been demonstrated for other Ca2 + influx inhibitors (Casteels & Droogmans, 1985;Aaronson & Jones, 1985). In contrast with these observations, it was demonstrated that high concentrations (30 and 100 yM) of pinacidil had little or no effect on 80mM K+-induced contractions in rat aorta (Bray et al, 1987; C) Macmillan Press Ltd, 1990 Weston et al, 1988).…”
Section: Introductioncontrasting
confidence: 46%
“…86Rb has been used as a marker of K conductance in smooth muscles (Imaizumi & Watanabe, 1981;Bolton & Clapp, 1984;Hamilton et al, 1986;Quast & Baumlin, 1988 (Bolton & Clapp, 1984;Casteels & Droogmans, 1985;Aaronson & Jones, 1985; see also this paper, Figures 5 and 6). On the other hand, the inhibition by drugs of transmembrane Ca2+ influx is associated with the closing of Ca2"-activated K+ channels (Casteels & Droogmans, 1985;Aaronson & Jones, 1985; see also this paper, Figures 5 and 6). In fact, pinacidil produced relaxation in strips contracted by 65.9mm K+, whereas cromakalim did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, appears extremely unlikely in this situation as only a 15min incubation with the lowest effective concentration of EGTA (0.1mM) was used. A reduction in the noradrenaline or histamine response could also be caused by membrane instability as a result of Ca2+ removal: this can be prevented by the inclusion of MgCl2 (10mM) (Aaronson & Jones, 1985). In preliminary experiments of the present series (unpublished), the inclusion of MgCl2 (10mM) did not prevent the large reduction in response to noradrenaline or histamine after Ca2+ removal.…”
Section: Discussionmentioning
confidence: 70%
“…4 Our laboratory recently reported that NE stimulated a Ca 2 + -dependent 42 K + efflux from rat 5 and rabbit aorta. 6 2 mixture to obtain a pH of 7.4. Propranolol (3 fiM) (Sigma Chemical Co., St. Louis, Mo.…”
Section: Camentioning
confidence: 99%